Peran Kontrol Diri Dalam Memoderasi Penggunaan Media Sosial dan Konformitas Terhadap Pembelian Impulsif Siswa SMA - Murniawaty, Indri; Sari, Nurul Aisah Lancar; Farliana, Nina (Universitas Negeri Semarang, 2023)
Impulse buying is an act of buying that is carried out spontaneously, without any planning or considerations with feelings of pleasure that can have a negative impact. The purpose of this study was to analyze the influence of the use of social media and conformity on impulsive buying with self-control as a moderating variable in SMA Negeri throughout Rembang Regency. This type of research uses a quantitative approach, with a population of 3048 students. The research sample was 100 students, with the sampling method using proportional random sampling. Data collection techniques using a questionnaire. Data analysis techniques used descriptive statistics and PLS-based Structural Equation Modeling (SEM). The results of the descriptive analysis show that the variable categories of impulsive buying and conformity are sufficient, while the variable categories of social media use and self-control are high. The results of the study show that the use of social media has a positive and significant effect on impulse purchases. Conformity has a positive and significant effect on impulsive buying. Self-control is not able to weaken the influence of social media use on impulse buying. Self-control is not able to weaken the effect of conformity on impulse buying. The advice given is that students should have careful planning and consideration in terms of purchasing decisions.